La violencia de un olvido - Olga Grau Duhart (Caravelle)
The aim of this article, “The violence of an oblivion” is to think about violence related to two types of oblivion. One of them refers to girls and boys sexual desire and associated disturbances; the other one to a political oblivion connected with human rights violations during Pinochet military dictatorship which has not been granted any justice. Even though both oblivions are of a different type, they represent ways of cultural and political violence. In this article I will refer to the two types of oblivion published in some national and cultural productions.